OXIDATIVE STRESS IN RAM SEMEN AND ANTIOXIDANT TREATMENT - R. Repkina-Nikolova (Trakia Journal of Sciences)
The oxidative stress constitutes accumulation of free radicals (FR) in the mammalian cells and tissue. Elevated accumulation of reactive oxygen species (subset of free radicals that contain oxygen) lead to a number of pathological abnormalities in cellular functioning respective to cells and organ damage. Excessive reactive oxygen species (ROS) formation can induce significant changes in sperm morphology, vitality, and oocyte fertizability. Spermatozoa membrane is composed of polyunsaturated fatty acids, which undergo oxidation under the action of free radicals. These processes result in reduced motility and impaired ability of sperm to fertilize the ovum. The antioxidants are the natural inhibitors of ROS activity. In the semen, they are found in large quantities in the seminal plasma. Their biological role is to attenuate the damaging effects of ROS. Low amounts of ROS are involved in the normal physiological and metabolic processes of the animal organism. Various reasons related to rearing, feeding and exploitation of the male animals can cause their overproduction. The imbalance between natural antioxidants and ROS production and accumulation result into body falling into the so-called oxidative stress (OS). This effect negative on various cell organelles. Damage to the sperm plasma membrane is caused by an imbalance between reactive oxygen species and antioxidants, which occurs especially during the semen processing (dilution, freeze-thaw). The aim of this literature review is to summarize the mechanism of influence of the oxidative stress and the possibilities to reduce its harmful effect over the ram semen parameters after chilling or freezing process.